Global space-time patterns of sub-daily extreme precipitation and its relationship with temperature and wind speed - Yichi Zhang; Xushu Wu (Environmental Research Letters, 2025)
Sub-daily extreme precipitation events can present significant risks such as flooding and soil erosion. Yet the space time pattern of such events on a global scale and their relationships with temperature and wind speed are not well understood. Based on over 9000 global meteorological stations and multi-source weighted-ensemble precipitation covering the warm seasons of 1980–2022, the characteristics and trends in sub-daily extreme precipitation (3 h time interval) were examined and their relationships with temperature and wind speed were explored across global major river basins. The results revealed a similar spatial pattern in the annual frequency, intensity, duration, and total amount of 3 h extreme precipitation events, though notable discrepancies were observed in specific regions such as Southeast Asia and eastern North America. Over half of the stations, particularly in South America, exhibited decreasing trends in extreme precipitation frequency, while significant increases were documented in Europe and Southeast Asia. The relationship between extreme precipitation intensity and temperature over different river basins exhibited diverse behaviors, characterized by monotonic increase (sub-daily Clausius–Clapeyron scaling, mostly in Europe), hook structure (mostly in North America), monotonic decrease (mostly in Africa), and nearly constant (mostly in Mid East, South Africa and South America). Moreover, wind speed generally increased with extreme precipitation intensity for tropical and subtropical basins, while in high-latitude basins strong winds tended to occur with lower precipitation intensity. These insights are vital for improving resilience against sub-daily extreme precipitation.